Lipopolysaccharide Is Transferred from High-Density to Low-Density Lipoproteins by Lipopolysaccharide-Binding Protein and Phospholipid Transfer Protein - Levels, J. H. M. (American Society for Microbiology, 2005)
Lipopolysaccharide (LPS), the major outer membrane component of gram-negative bacteria, is a potent endotoxin that triggers cytokine-mediated systemic inflammatory responses in the host. Plasma lipoproteins are capable of LPS sequestration, thereby attenuating the host response to infection, but ensuing dyslipidemia severely compromises this host defense mechanism. We have recently reported that Escherichia coli J5 and Re595 LPS chemotypes that contain relatively short O-antigen polysaccharide side chains are efficiently redistributed from high-density lipoproteins (HDL) to other lipoprotein subclasses in normal human whole blood (ex vivo). In this study, we examined the role of the acute-phase proteins LPS-binding protein (LBP) and phospholipid transfer protein (PLTP) in this process. By the use of isolated HDL containing fluorescent J5 LPS, the redistribution of endotoxin among the major lipoprotein subclasses in a model system was determined by gel permeation chromatography. The kinetics of LPS and lipid particle interactions were determined by using Biacore analysis. LBP and PLTP were found to transfer LPS from HDL predominantly to low-density lipoproteins (LDL), in a time- and dose-dependent manner, to induce remodeling of HDL into two subpopulations as a consequence of the LPS transfer and to enhance the steady-state association of LDL with HDL in a dose-dependent fashion. The presence of LPS on HDL further enhanced LBP-dependent interactions of LDL with HDL and increased the stability of the HDL-LDL complexes. We postulate that HDL remodeling induced by LBP- and PLTP-mediated LPS transfer may contribute to the plasma lipoprotein dyslipidemia characteristic of the acute-phase response to infection.